Protective effects of GPR37 via regulation of inflammation and multiple cell death pathways after ischemic stroke in mice. Issue 10 (3rd July 2019) - McCrary, Myles R.; Jiang, Michael Q.; Giddens, Michelle M.; Zhang, James Y.; Owino, Sharon; Wei, Zheng Z.; Zhong, Weiwei; Gu, Xiaohuan; Xin, Huang; Hall, Randy A.; Wei, Ling; Yu, Shan P.
ABSTRACT: GPCR 37 (GPR37) is a GPCR expressed in the CNS; its physiological and pathophysiological functions are largely unknown. We tested the role of GPR37 in the ischemic brain of GPR37 knockout (KO) mice, exploring the idea that GPR37 might be protective against ischemic damage. In an ischemic stroke model, GPR37 KO mice exhibited increased infarction and cell death compared with wild‐type (WT) mice, measured by 2, 3, 5‐triphenyl‐2H‐tetrazolium chloride and TUNEL staining 24 h after stroke. Moreover, more severe functional deficits were detected in GPR37 KO mice in the adhesive‐removal and corner tests. In the peri‐infarct region of GPR37 KO mice, there was significantly more apoptotic and autophagic cell death accompanied by caspase‐3 activation and attenuated mechanistic target of rapamycin signaling. GPR37 deletion attenuated astrocyte activation and astrogliosis compared with WT stroke controls 24–72 h after stroke. Immunohistochemical staining showed more ionized calcium‐binding adapter molecule 1–positive cells in the ischemic cortex of GPR37 KO mice, and RT‐PCR identified an enrichment of Ml‐type microglia or macrophage markers in the GPR37 KO ischemic cortex. Western blotting demonstrated higher levels of inflammatory factors IL‐1β, IL‐6, monocyte chemoattractant protein, and macrophage inflammatory protein‐1α in GPR37‐KO mice after ischemia. Thus, GPR37 plays a multifaceted role after stroke, suggesting a novel target for stroke therapy.—McCrary, M. R., Jiang, M. Q., Giddens, M. M., Zhang, J. Y., Owino, S., Wei, Z. Z., Zhong, W., Gu, X., Xin, H., Hall, R. A., Wei, L., Yu, S. P. Protective effects of GPR37 via regulation of inflammation and multiple cell death pathways after ischemic stroke in mice. FASEB J. 33, 10680–10691 (2019). www.fasebj.org